How to mitigate high risks to secure more high-quality protein? Joint technological innovation strategies for offshore mariculture considering different power structures - Xin Qi; Fengxuan Zhang; Ying Zhang; Mingxing Zheng; Yichong Dong (Aquaculture Reports)
Offshore Mariculture (OM) represents a novel approach to alleviating inshore environmental pressure while meeting the growing demand for high-quality protein. The potential for unforeseeable risk losses during the operational process has seriously hindered the development of this industry. To better address the developmental challenges of offshore mariculture, this study incorporates various power structures and the role of information sharing. Focusing primarily on mitigating risk losses, it constructs a differential game model involving research institutions and offshore mariculture enterprises (OME) under four decision-making modes: centralized decision-making, decentralized decision-making without cost-sharing, research institution–driven decentralized decision-making, and enterprise-driven decentralized decision-making. The model is then analyzed through numerical simulations. The results of the study reveal the following: (1) It is generally difficult for OME and research institutions to form a central decision-maker capable of achieving the optimal outcomes of centralized decision-making. However, the revenue of the mariculture decision-making system, the level of information sharing, and the reduction in risk losses under the centralized mode can serve as optimal benchmarks. Compared with non-cooperative decentralized decision-making, decision-making modes driven by either party are wiser choices. (2) The dominant party between OME and research institutions varies across different development stages. As the cost of mariculture-related efforts declines, all key indicators of the decision-making system improve significantly in the mature stage compared to earlier phases. At this stage, OME tend to take the lead, yet maintaining the R&D motivation of research institutions remains practically relevant. (3) In the mature phase of OM development, governments can achieve more desirable outcomes with relatively lower R&D funding. Therefore, while adhering to the original intention of fostering early-stage development, government support can become more flexible during the mature stage.